Tables for Eccentrically Loaded WT Shapes in Compression - Gordon, Mark E. (Engineering Journal, 2010)
WT shapes are often used for bracing, and they are typically connected to their supports with gusset plates on the flange. This attachment creates an eccentric axial load on the WT, which is not considered by design tables in the 13th edition AISC Manual of Steel Construction. This paper demonstrates one method for generating design tables that account for this eccentric loading.